Contemporary retroperitoneal lymph node dissection (RPLND) for testis cancer in the UK – a national study. (30th July 2016) - Wells, Hannah; Hayes, Matthew C.; O'Brien, Tim; Fowler, Sarah
Abstract : Objectives: To undertake a comprehensive prospective national study of the outcomes of retroperitoneal lymph node dissection (RPLND) for testis cancer over a 1‐year period in the UK. Patients and Methods: Data were submitted online using the British Association of Urological Surgeons Section of Oncology Data and Audit System. All new patients undergoing RPLND for testis cancer between March 2012 and February 2013 were studied prospectively. Data were analysed using Tableau software and case ascertainment compared with Hospital Episode Statistics data. Results: In all, 162 men underwent RPLND by 20 surgeons in 17 centres. The mean (range) case volume per centre was 9 (2–32) and the median (range) case volume per surgeon was 6 (1–30). Indications included: residual mass after chemotherapy (73%), primary treatment (6%), relapse (14%), and salvage (7%). The median time to surgery after chemotherapy was 8–12 weeks (<4 – >12 weeks) and 91% of procedures utilised open surgery. The median operating time was 3–4 h (<1.5 – >6 h). Nerve sparing was performed in 67% of patients (19% bilateral, 48% unilateral). The dissection was template in 81% and lumpectomy in 16%; 25% required additional intraoperative procedures including 11% synchronous planned nephrectomy. In all, 157/160 (98%) of recorded RPLND operations were completed. One was terminated due to bleeding and in two the mass could not be removed. There were no deaths within 30 days of surgery. In all, 75% of the men did not require a blood transfusion, 15% required 1–2 units and 10% received >2 units. There were postoperative complications in 10% of the men (Clavien–Dindo Grade I, seven men; Grade II, seven; and Grade III, one). The mean (range) length of stay was 5.5 (1–59) days. Histology showed necrosis in 22%; teratoma differentiated in 42%; and residual cancer in 36%. Conclusions: This prospective collaborative national study describes for the first time the surgical outcomes after RPLND across the UK. The quality of RPLND in the UK appears high. The study can act as a benchmark for this type of surgery across the world.